Hauntological engagements: Visual redress at Stellenbosch University (Journal of Student Affairs in Africa, 2024)
This article asks the central question of how to practically engage in the ongoing production of space at Stellenbosch University (SU) as to reimagine and redefine spaces. Spaces, which affect people indirectly and subconsciously, can act as microaggressions on one hand and places of safety connected to identity on the other. The Visual Redress (VR) project at SU focuses on removing or replacing contentious visual elements on campus and facilitating engagements to alter experiences ofplaces and spaces. The VR project is not only interested in physically transforming the space, but also in facilitating critical dialogue and physical interventions to engage in spatial memory and emotional remembrance. In this article Hauntology is used as a methodology to remember and reflect on visual elements on the Stellenbosch campus of SU and how the memory of the past and the dead in the form of visual elements still haunts the present. These hauntological engagements include crucial interactions with students, lecturers, and the various publics of the university. In this article the researchers will provide an overview of VR at SU and show and discuss the processes of three specific VR projects that were implemented at SU to illustrate the importance of hauntological engagements with the aim of reconstructing spaces.
Keywords: Hauntology; space; visual redress; Stellenbosch University; South Africa